IMPLEMENTASI KEBIJAKAN PENGELOLAAN SDM DI SEKOLAH DASAR - Herawati, Herawati; Lisa Safitri, Lisa Safitri; Safitri, Melinda Dwi; Arita Marini (Bajang Institute, 2024)
The study examines the impact of human resource management (HRM) on secondary schools, focusing on the challenges and opportunities in implementing SDM. It reveals that primary schools are more organized due to well-structured training programs and advanced facilities, but high pressure and insufficient support for teachers remain issues. Secondary schools face more serious problems, such as lack of resources, teachers, and educational facilities. The study also highlights the importance of school leadership in the success of SDM implementation. Schools with clear goals and the ability to coordinate all activities are more effective in implementing MDM. Active participation in the planning and evaluation process is crucial. The study emphasizes the importance of government support for teachers in vocational training and development, especially at district headquarters. The study contributes to the ongoing debate about HRM in education and emphasizes the need for a holistic and supportive approach to human resource management in schools.